The Effects of Compensation, and Organizational Climate on Employees’ Performance by Organizational Commitment - Husni Imron; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
HR's main challenge is how to build a performance culture, where employees can provide optimal performance. This study aims to determine the effect of compensation and organizational climate on organizational commitment and its influence on employee performance. One of the factors for good employee performance is high organizational commitment as well. Previous studies have suggested that compensation and organizational climate influence the organizational commitment. Also found that organizational commitment becomes one of the main factors that affect employee performance. This research was conducted by distributing questionnaires. The collected data is then processed using structure equational modelling with compensation and organizational climate as independent variables (X), employee performance as dependent variable (Y), and organizational commitment as intervening variables (Z). The findings showed that compensation and organizational climate has positive relationship with organizational commitment. This study also showed that only organizational climate, and organizational commitment has positive and significant relationship with employee performance because compensation has a negative significant relationship with employee performance.